KEEFEKTIFFAN PERMAINAN ENGKLEK DALAM MENGEMBANGKAN KEMAMPUAN MOTORIK KASAR ANAK USIA DINI - Dwiana Asih Wiranti; Diah Ayu Mawarti (Universitas Muria Kudus, 2018)
This research was aimed at 1) measuring the learning result of the early childhood's motor ability between pretest and posttest, 2) analyzing the effectiveness of engklek game in the development of gross motor ability for the early childhood; 3) describing the children's responses on engklek game in the development of gross motor ability for the early childhood. This research applied experimental design with one group pretest posttest design in answering the problem statements of the research. The location of the research was in RA Manbaul Ma'arif. The data analysis technique used to calculate the research result was t-test. The research result shows that the result of gross motor ability is improved after being given the treatment through engklek game. Engklek game is effective in improving the children's hard motor ability. It is proven by the fact that most of the children are in the criteria of Starting to Develop when pretest was conducted and the criteria of Developed Excellently after the posttest was conducted. In addition, the traditional game especially engklek received the positive response from the early childhood to be applied in the learning.